THE BRITISH COLONIAL POWER IN GEORGE ORWELL’S BURMESE DAYS - Zulkarnaen, Ryan; Ruminda, Ruminda; Awaludin, Lili (CALL, 2023)
This study tried to discover British colonial power in George Orwell’s Burmese Days. Gramsci's hegemony theory regarding to a concept of an integral state was applied. A qualitative descriptive method was used in the study. Data in the study were dialogues and narratives from historical contacts between British and Burmese regarding the British colonial regime. The data consisted intrinsic element of theme, and 2 extrinsic elements of political society and civil society. Both elements were structure in literary works, and represent the British colonial power in George Orwell’s Burmese Days. A theme of colonial was found among the element of fiction. There were extrinsic elements such as political society and civil society. The study concluded that the intrinsic elements forming a story that could representative how the British colonial power appeared on theme. The relationship of both elements form totality of meaning and integrity that how the British colonial power operations in George Orwell’ Burmese Days.  Keywords: colonialism, hegemony, integral state, orientalism